Street food in Dushanbe, Tajikistan: Availability and nutritional value - Albuquerque, G (2019)
Street food is part of the culture in central Asia. Although nourishing foods can be found, unhealthier options are becoming increasingly popular - a marker of nutrition transition. The nutritional composition of street foods in urban settings is, however, unknown. The objective of this study was, thus, to characterise the street food availability in Dushanbe, Tajikistan. A total of 800 street food vending sites in public markets were selected through random and systematic procedures. Trained interviewers collected data on vending sites' characteristics, location and food available. Samples of the most commonly available foods were collected (99 homemade and 35 industrial). Macronutrients were quantified through proximate analysis. Fruit, drinks and foods other than fruit were available, respectively, in 4.5%, 40.5%, and 87.4%, of the vending sites. Among the latter, 63.6% sold only homemade (e.g., bread, traditional dishes, snacks, pastries, sandwiches and cakes), 19.3% only industrial (e.g., bread, snacks, pastries and cookies) and 17.1% both types of food. Homemade foods presented higher energy per serving than industrial foods (median kcal/serving: 452 vs 276, p<0.001). A high content in saturated (soup: 10.9 g/serving) and trans-fatty acids (cakes: 1.8 g/serving) was also found in homemade foods. However, the highest content in these fatty acids was found in industrial wafers (12.9 g/serving and 2.5 g/serving, respectively). Soft drinks were available in 68.5% of the vending sites selling beverages. Homemade and industrial street foods, with heterogeneous nutritional value, were widely available in Dushanbe. Policies promoting the availability of healthy foods should be encouraged.